Original Antigenic Sin Shapes the Immunological Repertoire Evoked by Human Cytomegalovirus Glycoprotein B/MF59 Vaccine in Seropositive Recipients. (27th February 2019) - Baraniak, Ilona; Kern, Florian; Holenya, Pavlo; Griffiths, Paul; Reeves, Matthew
Abstract: A human cytomegalovirus (HCMV) vaccine is urgently needed to protect against primary infection and enhance existing immunity in HCMV-infected individuals (HCMV + ). Using sera from HCMV + glycoprotein B/MF59 vaccine recipients prior to transplant, we investigated the composition of the immune response. Vaccination boosted preexisting humoral responses in our HCMV + cohort but did not promote de novo responses against novel linear epitopes. This suggests that prior natural infection has a profound effect on shaping the antibody repertoire and subsequent response to vaccination ("original antigenic sin"). Thus, vaccination of HCMV + may require strategies of epitope presentation distinct from those intended to prevent primary infection. Abstract : Vaccination of human cytomegalovirus–infected individuals with the glycoprotein B (gB) vaccine boosts preexisting immune responses against gB but fails to induce new responses against novel linear epitopes within gB in seropositive individuals.